THE INFLUENCE OF INDIGENOUS LEADERSHIP AND TOURISM AWARENESS WORK CULTURE ON THE DEVELOPMENT OF TOURISM VILLAGES IN BATU ANJAU, LALAN NAGARI, SIJUNJUNG REGENCY: PENGARUH INDIGENIOUS LEADERSHIPS DAN BUDAYA KERJA SADAR WISATA TERHADAP PENGEMBANGAN DESA WISATA DI BATU ANJAU NAGARI LALAN KABUPATEN SIJUNJUNG - Dwi Mulya Kartini; Aldri Frinaldi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The purpose of this study was to determine the effect of indigenous leadership and tourism-aware work culture on the development of tourist villages in Batu Anjau, Lalan Village, Sijunjung Regency. The research method is quantitative. The number of research respondents was 118 people with a sample of 91 respondents. The instrument used in this study was a questionnaire compiled based on a Likert scale. The data analysis technique for this study was descriptive analysis, regression testing, hypothesis testing and data confirmation. Indigenous leaderships and tourism-aware work culture have a positive and significant effect on the development of tourist villages in Batu Anjau, Lalan Village, Sijunjung Regency. Thus, the hypothesis proposed by the researcher was empirically tested because the variables indigenous leaderships and tourism-aware work culture have an effect on the development of tourist villages.